Responsive Neurostimulation Effects Significant Seizure Reduction Without Resection in Medically Refractory Epilepsy Involving Occipital Networks. A Retrospective Review of a Case Series - Oster, Joel M; Kryzanski, James T (Medical Research Archives, 2023)
Objective: The goal of this work is to retrospectively and qualitatively describe a case series of two (2) patients with Occipital Epilepsy Networks treated with Responsive Neurostimulation Method: A retrospective qualitative review of two (2) clinical cases is presented and clinicopathologic features and quantitative Responsive Neurostimulation datasets and associated variables are analyzed for review Results: Significant and incremental seizure reduction occurred post RNS placement and this report highlights these 2 cases.  One patient exhibited no seizures subsequently 2.5 years post Responsive Neurostimulation placement (Engel class I) and another patient became almost free of seizures except for the occurance of fleeting and occasional visual auras approximately 2 years post Responsive Neurostimulation placement (Engel class II).  This report highlights that these 2 cases exhibited good clinical outcome after Responsive Neurostimulation placement for epilepsy localized to onset zones in occipital networks.